Challenges and opportunities for neonatal respiratory support in Nigeria: a case for regionalisation of care - Okolo AA; Okonkwo IR; Ideh RC (Nigerian Journal of Paediatrics, 2024)
Background: Neonatal health appears not to have received the deserved attention in the context of the Child Surviva lStrategies and this must have contributed to the non-attainment of the MDG-4 in Nigeria. Neonatalmortality contributes 40% or more to the current rate of child deaths globally, with birth asphyxia, prematurity and its complications and severe infections as the leading causes. This emphasises the need to re-focus on neonatal health. Given the state of the economy in the low- and middle-income countries, Nigeria, like most of the other countries lack the resources required for efficient neonatal health care with minimal attention on the strategies needed to address the major causes of newborn death.